Body, Space, and Sensations in Edgar Allan Poe’s “A Predicament” - SHU-TING KAO, Justine (Anafora, 2023)
This paper aims to examine the sensationalism of Blackwood’s Magazine as evident in Poe’s tale “A Predicament” and how Poe disengages from the tradition of Blackwoods. On the one hand, Poe conflates Psyche Zenobia’s adventure into a Gothic Cathedral with the Blackwood’s sensationalistic experience, which treats vehement sensations as the prime condition for stimulating the mind’s engagement with a spiritual vision of a world beyond the material world. On the other, Poe’s tale disengages itself from the tradition of Blackwood’s Magazine: Zenobia loses her sensations altogether in the quest for final knowledge and there is no return to her real life. This paper will further look at the mutilated/deformed body in Poe’s “A Predicament” as a body in pain, or without pain, through which the mind engages its imagination. It will also discuss how Poe, through Zenobia’s gaze and speculation upon a sublime cathedral, installs an aesthetic appreciation that distances an imaginary space from reality and facilitates self-mesmerism through which Zenobia is grounded in the earthly world, both physically and spiritually.